A Comparison of Two Stories of People Motivated by the Rejection of the Love of Roro Jonggrang and Sangkuriang and its Implications in Narrative Text Language Learning - Dede Narawaty (Scope : Journal of English Language Teaching, 2023)
The focus of this research is the study of two folklores entitled Roro Jonggrang (the origin of Prambanan temple) from Central Java and Sangkuriang (the origin of Tangkuban Perahu Mountain) from West Java. This research was a qualitative research with comparative study techniques. The method used in this research was a descriptive method. Data were analyzed using a qualitative approach to content analysis techniques.The research findings indicate that there are some similarities and differences between the folklores in terms of characters, characterizations, settings, themes and moral values.